Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure! Let's solve each part of the question, step by step.
### Part 7: Finding [tex]\( g(-12) \)[/tex]
Given the function [tex]\( g(x) = 1 - \frac{3}{4} x \)[/tex], we need to find [tex]\( g(-12) \)[/tex].
1. Substitute [tex]\( x = -12 \)[/tex] into the function:
[tex]\[ g(-12) = 1 - \frac{3}{4} (-12) \][/tex]
2. Calculate the value inside the function:
[tex]\[ g(-12) = 1 - (-9) \][/tex]
3. Simplify:
[tex]\[ g(-12) = 1 + 9 \][/tex]
[tex]\[ g(-12) = 10 \][/tex]
So, [tex]\( g(-12) = 10.0 \)[/tex].
### Part 8: Finding [tex]\( g(0) \)[/tex]
Next, we need to find [tex]\( g(0) \)[/tex].
1. Substitute [tex]\( x = 0 \)[/tex] into the function:
[tex]\[ g(0) = 1 - \frac{3}{4} (0) \][/tex]
2. Calculate the value inside the function:
[tex]\[ g(0) = 1 - 0 \][/tex]
3. Simplify:
[tex]\[ g(0) = 1 \][/tex]
So, [tex]\( g(0) = 1.0 \)[/tex].
### Part 9: Finding [tex]\( -5 \cdot g(4) -1 \)[/tex]
Finally, we need to find the value of [tex]\( -5 \cdot g(4) - 1 \)[/tex].
1. First, find [tex]\( g(4) \)[/tex] by substituting [tex]\( x = 4 \)[/tex] into the function:
[tex]\[ g(4) = 1 - \frac{3}{4} (4) \][/tex]
2. Calculate the value inside the function:
[tex]\[ g(4) = 1 - 3 \][/tex]
3. Simplify:
[tex]\[ g(4) = -2 \][/tex]
Now substitute this value into the expression [tex]\( -5 \cdot g(4) - 1 \)[/tex]:
4. Substitute [tex]\( g(4) = -2 \)[/tex] into the expression:
[tex]\[ -5 \cdot (-2) - 1 \][/tex]
5. Calculate the value:
[tex]\[ 10 - 1 \][/tex]
6. Simplify:
[tex]\[ 9 \][/tex]
So, [tex]\( -5 \cdot g(4) - 1 = 9.0 \)[/tex].
Therefore, the answers are:
1. [tex]\( g(-12) = 10.0 \)[/tex]
2. [tex]\( g(0) = 1.0 \)[/tex]
3. [tex]\( -5 \cdot g(4) - 1 = 9.0 \)[/tex]
### Part 7: Finding [tex]\( g(-12) \)[/tex]
Given the function [tex]\( g(x) = 1 - \frac{3}{4} x \)[/tex], we need to find [tex]\( g(-12) \)[/tex].
1. Substitute [tex]\( x = -12 \)[/tex] into the function:
[tex]\[ g(-12) = 1 - \frac{3}{4} (-12) \][/tex]
2. Calculate the value inside the function:
[tex]\[ g(-12) = 1 - (-9) \][/tex]
3. Simplify:
[tex]\[ g(-12) = 1 + 9 \][/tex]
[tex]\[ g(-12) = 10 \][/tex]
So, [tex]\( g(-12) = 10.0 \)[/tex].
### Part 8: Finding [tex]\( g(0) \)[/tex]
Next, we need to find [tex]\( g(0) \)[/tex].
1. Substitute [tex]\( x = 0 \)[/tex] into the function:
[tex]\[ g(0) = 1 - \frac{3}{4} (0) \][/tex]
2. Calculate the value inside the function:
[tex]\[ g(0) = 1 - 0 \][/tex]
3. Simplify:
[tex]\[ g(0) = 1 \][/tex]
So, [tex]\( g(0) = 1.0 \)[/tex].
### Part 9: Finding [tex]\( -5 \cdot g(4) -1 \)[/tex]
Finally, we need to find the value of [tex]\( -5 \cdot g(4) - 1 \)[/tex].
1. First, find [tex]\( g(4) \)[/tex] by substituting [tex]\( x = 4 \)[/tex] into the function:
[tex]\[ g(4) = 1 - \frac{3}{4} (4) \][/tex]
2. Calculate the value inside the function:
[tex]\[ g(4) = 1 - 3 \][/tex]
3. Simplify:
[tex]\[ g(4) = -2 \][/tex]
Now substitute this value into the expression [tex]\( -5 \cdot g(4) - 1 \)[/tex]:
4. Substitute [tex]\( g(4) = -2 \)[/tex] into the expression:
[tex]\[ -5 \cdot (-2) - 1 \][/tex]
5. Calculate the value:
[tex]\[ 10 - 1 \][/tex]
6. Simplify:
[tex]\[ 9 \][/tex]
So, [tex]\( -5 \cdot g(4) - 1 = 9.0 \)[/tex].
Therefore, the answers are:
1. [tex]\( g(-12) = 10.0 \)[/tex]
2. [tex]\( g(0) = 1.0 \)[/tex]
3. [tex]\( -5 \cdot g(4) - 1 = 9.0 \)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.